Strengthening charity regulation in England and Wales? The Charities (Protection and Social Investment) Act 2016 and the impact of academic witnesses. (23rd March 2017) - Morgan, GarethG.; Morris, Debra
Abstract : Research on charity regulation is frequently triggered by charity law developments. However, it is often unclear what impact such research has on policy makers and parliamentarians shaping charity regulation. Both authors of this paper were called to give evidence to the Parliamentary Joint Committee examining the draft Bill that led to the Charities (Protection and Social Investment) Act 2016. We review the possible impact of our evidence on the ultimate Act and on charity regulation more broadly.